Effects of sleep and insomnia on cardiovascular disease - literature review - Gmitrzuk, Julita; Karasiński, Maciej; Malinka, Zuzanna; Wiśniewska, Katarzyna; Jachymek, Anna; Opatowska, Martyna; Jakubiec, Joanna; Kucharski, Tomasz (Quality in Sport, 2024)
Introduction: Sleep disorders, including insomnia, obstructive sleep apnea (OSA) and other sleep disorders, are increasingly recognized as important risk factors for cardiovascular diseases such as hypertension and coronary artery disease. This review aims to analyze the current literature on the impact of sleep disorders on cardiovascular health, focusing on the underlying pathophysiological mechanisms and the effectiveness of diagnostic and therapeutic approaches. The results highlight the importance of early diagnosis and treatment of sleep disorders to reduce cardiovascular risk. Aim of the Study: The main objective of this study is to review and summarize recent findings on the relationship between sleep disorders and cardiovascular diseases, with a particular focus on hypertension and coronary artery disease. This study aims to elucidate the pathophysiological mechanisms linking these conditions and to evaluate the effectiveness of current diagnostic and therapeutic strategies. Materials and Methods: This review was conducted by searching PubMed for articles published in the last ten years (2014-2024) using keywords such as „insomnia”, „obstructive sleep apnea”, „hypertension”, „coronary heart disease”, „polysomnography”. Conclusions: The evidence reviewed in this article suggests that sleep disorders are important and independent risk factors for cardiovascular disease. Insomnia, obstructive sleep apnea and other sleep disorders contribute to cardiovascular morbidity through mechanisms such as increased sympathetic activity, systemic inflammation and metabolic dysregulation. Effective diagnosis and treatment of sleep disorders, including the use of CPAP therapy for obstructive sleep apnea and cognitive-behavioral therapy for insomnia, can mitigate these risks and improve cardiovascular outcomes.